2022
DOI: 10.36349/easjpp.2022.v04i03.001
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Antioxidant and α–Amylase Inhibition Properties of Alligator Pepper (Aframomum Melegueta): A Potential Therapeutic Against Diabetes Mellitus

Abstract: Diabetes is a chronic metabolic disease characterized by raised levels of blood glucose, which over time leads to serious damage to the heart, blood vessels, eyes, kidneys, and nerves. α-amylase Plays a major role in the digestion of starch and glycogen. Thus, inhibitors of this enzyme delay the breakdown of carbohydrates in the small intestine, thereby diminishing postprandial blood glucose in the diabetic patient. In this study, a DPPH radical scavenging activity and computational approaches were employed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Another flavone hispidulin confirmed the stimulation of glucagon-like peptide-1 and suppressed hepatic glucose production in STZ-NA-induced diabetic rats [85]. Genkwanin is also a potent antioxidant that is responsible for α-amylase inhibitory activity [86]. A study by Ihim et al (2023) [87] reported that apigenin facilitates glucose-stimulated insulin secretion and prevents endoplasmic reticulum (ER) stress-mediated β-cell apoptosis in the pancreas.…”
Section: Active Compounds Of Ecuadorian Medicinal Plants and Their An...mentioning
confidence: 88%
See 1 more Smart Citation
“…Another flavone hispidulin confirmed the stimulation of glucagon-like peptide-1 and suppressed hepatic glucose production in STZ-NA-induced diabetic rats [85]. Genkwanin is also a potent antioxidant that is responsible for α-amylase inhibitory activity [86]. A study by Ihim et al (2023) [87] reported that apigenin facilitates glucose-stimulated insulin secretion and prevents endoplasmic reticulum (ER) stress-mediated β-cell apoptosis in the pancreas.…”
Section: Active Compounds Of Ecuadorian Medicinal Plants and Their An...mentioning
confidence: 88%
“…Stimulates glucagon-like peptide-1 and suppresses hepatic glucose production [85] Genkwanin Flavonoid α-amylase inhibitory activity and antioxidant activity [86] Apigenin Flavonoid…”
Section: Cirsimaritin Flavonoidmentioning
confidence: 99%
“…Another flavone hispidulin confirmed the stimulation of glucagon-like peptide-1 and suppressed hepatic glucose production in STZ-NA-induced diabetic rats [ 102 ]. Genkwanin is also a potent antioxidant that is responsible for α-amylase inhibitory activity [ 103 ]. A study by Ihim et al (2023) [ 104 ] reported that apigenin facilitates glucose-stimulated insulin secretion and prevents endoplasmic reticulum (ER) stress-mediated β-cell apoptosis in the pancreas.…”
Section: Bioactive Compounds Of Ecuadorian Medicinal Plants and Their...mentioning
confidence: 99%
“…The phenylpropene, namely, estragole (methyl chavicol), acts as an enzyme inhibitor against α-amylase, lipase, and tyrosinase and serves as a potent antioxidant agent that can improve diabetes [ 127 , 128 ]. This bioactive compound is also found in Foeniculum vulgare [ 103 ]. n-Hexacosane is a natural alkane that improves blood glucose levels, glucose tolerance, glycated hemoglobin, and liver glycogen [ 129 ] found in Physalis peruviana [ 118 ].…”
Section: Bioactive Compounds Of Ecuadorian Medicinal Plants and Their...mentioning
confidence: 99%
See 1 more Smart Citation